Neutrophil-Lymphocyte Ratio and Procalcitonin as Predictors of the Severity of Acute Pancreatitis - Dessy Iriana; Ani Kartini; Yuyun Widaningsih; Agus Alim Abdullah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
The Neutrophil-Lymphocyte Ratio (NLR) and procalcitonin are used to indicate systemic inflammation in various medical disorders. Both parameters were determined in this study to predict the severity of acute pancreatitis. This study was a cross-sectional study using a retrospective approach to patients diagnosed with acute pancreatitis by using medical record data from patients at Dr. Wahidin Sudirohusoso Hospital, Makassar, from January 2014 to May 2019. This study comprised 35 patients hospitalized with acute pancreatitis, with a similar proportion of males and females. This study discovered that the mean age in this study was 44.17±12.9 years. The most prevalent cause was Gallstones (77.1%), the most severe degree was mild (54.2%), and the highest outcome was survival (77.1%). The NLR (9.93±11.19, p=0.011) increased in proportion to severity. However, additional analysis based on classification of disease severity revealed that only mild-severe NLR was significant (p=0.005). Procalcitonin (8.13±11.25, p=0.001) increased along with the increased disease severity, and the subsequent analysis showed that the distribution of severity was similar. The NLR can predict the severity of acute pancreatitis but is less effective than procalcitonin. This study required a more proportional subject population and consideration of other factors.